Continuous Prophylactic Antiretrovirals/Antiretroviral Therapy Since Birth Reduces Seeding and Persistence of the Viral Reservoir in Children Vertically Infected With Human Immunodeficiency Virus. (5th June 2020) - Massanella, Marta; Puthanakit, Thanyawee; Leyre, Louise; Jupimai, Thidarat; Sawangsinth, Panadda; de Souza, Mark; Suntarattiwong, Piyarat; Kosalarksa, Pope; Borkird, Thitiporn; Kanjanavanit, Suparat; Chokephaibulkit, Kulkanya; Hansudewechakul, Rawiwan; et al.
Abstract: Background: Early antiretroviral therapy (ART) restricts the size of the human immunodeficiency virus (HIV) reservoir in infants. However, whether antiretroviral (ARV) prophylaxis given to exposed vertically infected children exerts similar effects remains unknown. Methods: We measured total and integrated HIV DNA, as well as the frequency of CD4 T cells producing multiply spliced RNA (msRNA) after stimulation (inducible reservoir) in vertically infected Thai infants. Eighty-five infants were followed longitudinally for up to 3 years. We compared the size of the reservoir in children who received continuous ARV prophylaxis since birth vs those who never received or discontinued prophylaxis before initiating ART. We used samples from a cross-sectional cohort of 37 Thai children who had initiated ART within 6 months of life to validate our findings. Results: Before ART, levels of HIV DNA and the frequencies of cells producing msRNA were significantly lower in infants who received continuous ARV prophylaxis since birth compared to those in whom ARV prophylaxis was discontinued or never initiated ( P < .020 and P < .001, respectively). Upon ART initiation, total and integrated HIV DNA levels decayed significantly in both groups ( P < .01 in all cases). Interestingly, the initial differences in the frequencies of infected cells persisted during 3 years on ART. The beneficial effect of prophylaxis on the size of the HIV reservoir was confirmed in the cross-sectional study. Importantly, no differences were observed between children who discontinued prophylactic ARVs before starting ART and those who delayed ART initiation without receiving prior prophylaxis. Conclusions: Neonatal ARV prophylaxis with direct transition to ART durably limits the size of the HIV reservoir. Abstract : Continuous antiretroviral prophylaxis since birth restricts the seeding of cellular Human Immunodeficiency Virus (HIV) reservoirs. In addition, a direct transition from prophylaxis to fully suppressive antiretroviral therapy limits the persistence of the HIV reservoir.